Seeing you walk, forever. Conversation about photographs, archives, and political-sexual resistance (Palíndromo, 2026)
This conversation took place during the final stage of the production process for the book Verte caminar (Trazar, 2025), a work that compiles five years of documentation and advocacy for the Ballroom scene in Chile, as seen through the lens of dissident artist Forever. On this occasion, we exchanged impressions on liminal, deviant, and dissenting artistic trajectories within the more traditional fields of the arts and photography. In addition, we explored and reflected on other political-affective spaces that allow us to understand our/other personal trajectories as intimate legacies that spread through the streets, rehearsals, and temporary shelters shared with others, in times when they are increasingly scarce.
Keywords: forever; photography; archives; dissidence; ballroom